Antigen‐Specific β‐Chemokine Production and CD8+ T‐Cell Noncytotoxic Antiviral Activity in HIV‐2‐Infected Individuals - Ahmed, R. K. S.; Norrgren, H.; Da Silva, Z.; Blaxhult, A.; Fredriksson, E.‐L.; Biberfeld, G.; Andersson, S.; Thorstensson, R. (Scandinavian journal of immunology, 2005)
Human immunodeficiency virus‐2 (HIV‐2) is less pathogenic than HIV‐1, and the disease progression in HIV‐2‐infected individuals seems to be similar to that seen in HIV‐1‐infected long‐term nonprogressors. Cell‐mediated immune responses and the production of noncytotoxic CD8+ T‐cell antiviral factors (CAF) and β‐chemokines have been correlated to protection against HIV‐1 and associated with asymptomatic infection and slower disease progression. We investigated the antigen‐induced β‐chemokine production in HIV‐2‐infected patients living in Sweden and in Guinea‐Bissau. We also compared in vitro CD8+ T‐cell‐mediated noncytotoxic antiviral activity against β‐chemokine‐sensitive R5 virus (HIV‐1Bal) and β‐chemokine‐insensitive X4 virus (HIV‐1IIIB) in HIV‐2‐infected patients with that in HIV‐1‐infected patients. HIV‐2‐specific β‐chemokine production was demonstrated in a majority of the HIV‐2‐infected subjects. CD8+ T cells of both HIV‐1 and HIV‐2‐infected individuals suppressed R5 virus replication in vitro in a similar manner, while the inhibition of X4 virus replication seemed to be more frequent and of a higher magnitude among HIV‐2‐infected patients compared to HIV‐1‐infected subjects. Taken together, our results indicate that the production of CD8+ T‐cell noncytotoxic antiviral factors may contribute to the low transmission of the virus and slower disease progression in HIV‐2‐infected patients.